2017
DOI: 10.15252/embj.201797630
|View full text |Cite
|
Sign up to set email alerts
|

Whole chromosome loss and associated breakage–fusion–bridge cycles transform mouse tetraploid cells

Abstract: Whole chromosome gains or losses (aneuploidy) are a hallmark of ~70% of human tumors. Modeling the consequences of aneuploidy has relied on perturbing spindle assembly checkpoint (SAC) components, but interpretations of these experiments are clouded by the multiple functions of these proteins. Here, we used a Cre recombinase-mediated chromosome loss strategy to individually delete mouse chromosomes 9, 10, 12, or 14 in tetraploid immortalized murine embryonic fibroblasts. This methodology also involves the gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Consistent with these results, we speculate that telomere loss can induce dicentric chromosome formation or micronucleus formation as well as chromosome lagging. These data extend and underscore our previous findings concerning the implication of telomere dysfunction in HL chromosomal instability via B/F/B cycles and micronucleus formation [ 28 , 29 ]. Of note, we provide in this study the first complete karyotype of the L428 cell line and demonstrate the feasibility of cytogenetic analysis in a xenograft HL model.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with these results, we speculate that telomere loss can induce dicentric chromosome formation or micronucleus formation as well as chromosome lagging. These data extend and underscore our previous findings concerning the implication of telomere dysfunction in HL chromosomal instability via B/F/B cycles and micronucleus formation [ 28 , 29 ]. Of note, we provide in this study the first complete karyotype of the L428 cell line and demonstrate the feasibility of cytogenetic analysis in a xenograft HL model.…”
Section: Discussionsupporting
confidence: 90%
“…However, recent studies using genetic engineering have revealed the possibility of performing aneuploidy therapy in cultured cells. Here, we summarize some of the main studies aimed at eliminating an entire chromosome using the Cre/loxP system [79][80][81][82][83][84][85], the TKneo transgene for positive and negative antibiotic selection [86], CRISPR/Cas9 system-mediated multiple cleavage [87,88], and zinc finger nuclease (ZFN)-mediated knock-in of the XIST gene to silence one copy of chromosome 21 [89] (cited in Table 2).…”
Section: Gene Targeting-mediated Chromosome Eliminationmentioning
confidence: 99%
“…Moreover, Matsumura et al [85] applied a chromosome elimination cassette (CEC), featuring fluorescent-protein and puromycin resistance genes surrounded by inverted loxP sites into chromosome deletions in cultured cells in vitro. Mouse tetraploid (4n = 80,XXXY) ES cells fused with two diploid ES cells differentiated but did not proliferate [79,85]. The elimination of two copies of chromosome 6 tagged with CEC in the tetraploid ES cells enabled survival in an undifferentiated state and the capability of teratoma formation, implying that chromosome 6 including the Nanog gene is indispensable for the self-renewal and pluripotency of mouse ES cells.…”
Section: Cre/loxp System-mediated Chromosome Eliminationmentioning
confidence: 99%
“…The rearrangement of chromosomes through the breakage‐fusion‐bridge (BFB) cycles may be one more feasible source of aneuploidy . BFB is a mechanism initiated by shortened and defective telomeres or when a chromosome subjected to a double‐stranded break (DSB) replicates and the sister chromatids join at their ends.…”
Section: Mechanisms Of Aneuploidymentioning
confidence: 99%